The Need for Computer Ethics Course for the Students of CSE/CS or Equivalent Discipline in Bangladesh - Islam, Md Monirul; Alam, Mohammed Shamsul; Ahsan, Tanveer (IIUC Studies, 2015)
Ethics has long been a part of engineering education and practices. Computer Science and Engineering (CSE) is not an exception. In this study, however, it was revealed that very few universities of Bangladesh have a course on Computer Ethics in their respective curriculum of Computer Science and Engineering. But the scenario of other countries are completely different; many universities in the world offer courses like Computer Ethics, Social and Ethical Implications of Computing or courses with similar title and content. There is an increasing trend towards teaching ethics as a major course within CSE departments. This paper examines the necessity of incorporating a Computer Ethics course in the curriculum of CSE in the universities of Bangladesh and suggests an outline for the course. It suggests some topics that can be covered in a Computer Ethics course and offers some practical suggestions also for making the course an effective one. This study also examines ethics in computer education in the light of the Holly Quran and the Sunnah of the Prophet Muhammad (S). IIUC Studies Vol.9 December 2012: 307-322